Adoption of a loyalty program through a mobile application: analysis of the Supermercados Meu Econômico case using the Basket Analysis - de Souza Junior, Wanderley (2020)
Objective: evaluate the impact of using a loyalty program in an online sales system on a mobile platform on customer loyalty in a neighborhood supermarket chain.Method: The data were analyzed using the technique of Basket Analysis using RapidMiner software and programming Python, with the objective of, via data mining of purchase coupons, establishing associations between products purchased by customers.Originality / Relevance: This article presents empirical evidence of increased customer loyalty through the implementation of a mobile platform in a supermarket chain in Palmas-TO.Results: As a result, it was possible to verify that the customer who used the loyalty program had an average ticket 11.4% higher than those who did not. It was also found that the average ticket for sales made by the application was 3.98 times higher than that of the physical store.Theoretical contributions: Previous work offers evidence of the effectiveness of traditional loyalty programs, but the effects specifically of loyalty programs specifically in a mobile environment and in the context of Brazilian retail are unknown. The case study shows that if adaptations are made to the store's supply process, the instrument proves to be highly effective.Contributions to management: The article demonstrates that, in the case of the supermarket chain Meu Econômico, the introduction of a mobile platform led to the conquest and loyalty of new customers, as well as the loyalty of old customers, by offering an innovative shopping experience. Other small and medium-sized retailers, particularly in supermarkets, could develop their mobile platforms as a means of building customer loyalty.